A study on the physico-chemical changes occurring in the milk fat during preparation of paneer - D.Aghav, Ashok; Gandhi, Kamal; Upadhyay, Neelam; Kumar, Anil; Lal, Darshan (Indian Journal of Dairy Science, 2014)
The changes taking place in milk fat during preparation of paneer from cow and buffalo milks were studied in three different seasons. Milk fat from samples, was extracted with chloroform using soxhlet-extraction method. The solvent was evaporated using vacuum evaporator followed by nitrogen flushing. The extracted fat samples were analysed for Reichert- Meissl, Polenske, saponification and iodine value, Butyro- refractometer reading at 40Â°C and free fatty acids (% oleic acid). The study revealed an increase in free fatty acid content during conversion of milk in to paneer, while small changes were observed in other physico-chemical properties of milk fat during preparation of paneer from raw milk.